ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI JOB STRESS SERTA PENGARUHNYA TERHADAP KEPUASAN KERJA DAN KINERJA SALESMAN (STUDI KASUS PADA PT. ADIRA FINANCE CABANG BANGKONG SEMARANG) - Agus Setyono; Mudji Rahardjo; Rini Nugraheni; Edy Rahardja (Faculty of Economics and Business Diponegoro University, 2012)
ABSTRACT The problem about job stress it seems becomes an interesting perspective together with the increase of the more and more complex challenge and competition. This research aims to evaluate the influence of the organizational and individual stressor to the job stress and also the effect to the job satisfaction and performance. To test the research hypothesis’ , 140 employees of PT. Adira Finance Bangkong Semarang Branch Office was asked to answer questionnaires about their perceptions of the organizational stressor, individual stressor, job stress, job satisfaction, and performance. The data acquired was analyzed using the Structural Equation Model (SEM). The result of this analysis, known that the Structural Equation Model has fulfilled the Goodness of Fix Index criteria: chi square = 162.200, probability = 0.522, RMSEA = 0.055, GFI = 0.950, AGFI = 0.912, TLI = 0.967, CFI = 0.977. The hypothesis testing shows that organizational stressor have an effect on the job stress, individual stressor have an effect on the job stress, the job stress have an effect on the job satisfaction, and the job stress have an effect on the performance. Based on the results, managerial implication suggest that the job satisfaction and performance can be improved by manage the job stress which is done by the company through stress management and by individual through counseling. Key words : organizational stressor; individual stressor; job stress; job satisfaction; performance